Implementation of Domestic Waste Management Policy in Batam City: Weimer And Vining Perspective - Ni Made Oveta Annisya; Ida Widianingsih; Budhi Gunawan (Dinasti Research, 2026)
The city of Batam faces challenges in managing domestic waste, marked by an increase in unmanaged waste. In response, the Batam City Government has issued Batam Mayor Regulation No. 5 of 2023 concerning Regional Policies and Strategies for the Management of Household Waste and Household-like Waste, which serves as a reference for domestic waste management. However, the situation on the ground shows that the waste problem has not yet been resolved. This study aims to examine the factors that influence the implementation of this policy, using the policy implementation theory perspective of Weimer and Vining (2010), which examines the aspects of policy logic, support, essential elements, and implementer capabilities. This study uses a qualitative approach with data collection techniques through in-depth interviews, observations, and document analysis at the Batam City Environment Agency. The results of the study show that, logically speaking, the policy has not yet achieved its objectives. Political support exists, but financial support is still limited, as is technological support. Essential elements such as the transport fleet are not in prime condition, and landfill infrastructure is also limited. The implementers' capabilities are good and there is a clear division of roles. Recommendations that can be suggested are routine supervision and monitoring by environmental management agencies regarding policy implementation, improvement of waste handling and management infrastructure, and increased support and stakeholder participation through public-private partnerships and corporate CSR participation in domestic waste management.